Retail innovation reframed : how to transform operations and achieve purpose-led growth and resilience - Jude, Gareth (London: Kogan page, 2021)
"Retail is defined by disruption; companies either adapt or are replaced by those that will. More so than ever learning how to reframe your business, apply change and stay innovative is key to continued success and survival. Innovation is hard for any organization, even more so for retailers where executing retail basics can often be seen as enough. But the difference between success and failure is increasingly becoming the ability to reframe your approach to innovation and use it to win the competitive edge, as Retail Innovation Reframed explains. Changing your business operations to solve customers' biggest challenges is how established household names and emerging businesses now thrive. Featuring case studies including Walmart, Warby Parker, Starbucks and Amazon, Retail Innovation Reframed demonstrates how to weave innovation into the operating fabric your company to remain ahead of the curve. Start your journey to innovation and learn how to use change to succeed. Online resources include templates for testing and analyzing new innovations"--
Includes bibliographical references and index.
Keywords: Retail trade; Strategic planning; Organizational change